EFEKTIFITAS EKSTRAK ETANOL DAUN SAWI HIJAU (BRASSICA RAPA VAR. PARACHINENSIS) SEBAGAI PELEMBAB KULIT DENGAN SEDIAAN MASKER PEEL-OFF - Cahya, Cucu Arum Dwi; Syarifuddin, Aminah; Syukur, Ahmad Syukur (Jurnal FARMASIMED (JFM), 2019)
Green mustard plants can be formulater into peel-off masks to moisturize the skin, because based on previous research green mustard leaves cointain flavonoids as antioxidants which can moisturize the skin. The purpose of this study was to find out green mustard leaves can be formulated into peel-off mask preparations and to find out the preparation and to find out the preparation off peel off mask with etanol extract of green mustard leaves can moisturize the skin. This study uses an experimental method. Green mustard leaves are extracted by maceration. In this study, a skin analyzer was usee as a mesure of skin moisture level after using peel off mask from a variety of dosage formulations which were divided into 5 preparations, blank (without mask, 3%,4%,5%), postive control (using peel off masks on the market). The Anova test results show a sig value of 0,000 or p<0,005 so it is concluded that the variabel has a difference. The conclusion of this study proves that the ethanol extract of green mustard leaves can be used as a peel-off mask for skin moisturizer, where the higher the concentration of mustard leaf extract, the higher the moisture vlue of the skin.